FACTORS INFLUENCING THE LEARNING SUCCESS OF MASTER STUDENTS AT IPB BUSINESS SCHOOL (SB-IPB) - Maya Wulan Arini; DS Priyarsono; Rokhani Hasbullah (Indonesian Journal of Business and Entrepreneurship (IJBE), 2017)
Business School of IPB (SB-IPB) has a low level of completing of study for its master program students on-time. Based on the report of SB-IPB 2015, only 0.8% of students graduating in 2014/2015 successfully completed their study in the normal time of thesis writing. This study aims to identify what factors cause the students unable to complete their thesis on time, thus affecting their learning success. The primary data in this study came from interviews to the students of year 2011/2012, while the secondary data were obtained from the academic section of SB-IPB. Determination of the number of samples was done using slovin formula obtaining 80 students as the respondents. The data analysis method used was SEM with PLS method. The results of the research indicate that the indicator that has a dominant role on the student characteristics is employment status while the dominant role indicators on the process of thesis writing are the suitability of area of interest and the administrative process. The value of the characteristics of students significantly affecting the process of their thesis writing is-0.283, and this indicates that students who are full time workers have a number of constraints in their thesis writing process. Likewise, the process of the thesis writing has a significant influence on the success of the study i.e. 0.346, and it means that the easier the process of thesis writing, the greater the success of their study. The academic division is expected to be more active in controlling the students who are in the process of writing their thesis, especially for the class whose students work full time so that it can well support the learning success of the students.Keywords: business school, master program, success of the study, PLS, SEMABSTRAKMahasiswa program magister di sekolah bisnis IPB (SB-IPB) memiliki tingkat ketepatan penyelesaian studi yang masih rendah. Berdasarkan laporan SB IPB 2015, hanya 0.8% mahasiswa yang lulus tahun 2014/2015 berhasil menyelesaikan studi dalam waktu normal penyusunan tesis. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor apa saja yang menyebabkan mahasiswa terlambat menyelesaikan tesis yang berdampak pada keberhasilan studi. Data primer dalam penelitian ini bersumber dari wawancara kepada mahasiswa tahun angkatan 2011/2012, sedangkan data sekunder bersumber dari bagian akademik SB-IPB. Penentuan jumlah sampel menggunakan rumus slovin diperoleh 80 mahasiswa sebagai responden. Metode analisis data yang digunakan, yaitu SEM dengan metode PLS. Hasil penelitian menunjukkan bahwa Indikator yang berperan dominan terhadap karakteristik mahasiswa yaitu status pekerjaan, sedangkan indikator yang berperan dominan terhadap proses penyusunan tesis yaitu kesesuaian bidang minat dan proses administrasi. Karakteristik mahasiswa signifikan memengaruhi proses penyusunan tesis sebesar -0.283. Artinya, mahasiswa yang aktif bekerja akan menghambat proses penyusunan tesisnya. Demikian juga proses penyusunan tesis berpengaruh signifikan pada keberhasilan studi sebesar 0.346. Artinya, semakin mudah proses penyusunan tesis maka akan semakin menigkatkan keberhasilan studi. Divisi akademik diharapkan dapat lebih aktif mengontrol mahasiswa yang sedang dalam proses penyusunan tesis terutama pada kelas yang mayoritas aktif bekerja untuk menunjang keberhasilan studi mahasiswa yang lebih baik.Keywords: sekolah bisnis, program magister, keberhasilan studi, PLS, SEM